Faktor-faktor yang Mempengaruhi Keberhasilan Rehabilitasi Pasien Pasca Stroke - Agnes Bintang Kartika (Yayasan Pendidikan Medika Indonesia, 2022)
Stroke is a neurological deficit due to disturbances in the circulatory system in the brain that occur suddenly, resulting in focal or global injury to the central nervous system (CNS). One of the treatments for stroke patients that affects the patient's prognosis is medical rehabilitation. According to several studies, in the rehabilitation process there are several important factors that influence the success of rehabilitation. These factors need to be considered when the rehabilitation process for post-stroke patients is carried out. Factors that can affect the outcome of rehabilitation are patient characteristics including age, gender, education and occupation. In addition, patient psychology such as depression and motivation, comorbid illness and time to start rehabilitation can also affect rehabilitation outcomes in post-stroke patients.